PENGARUH KUALITAS PRODUK, HARGA DAN CITRA MEREK TEHADAP KEPUTUSAN PEMBELIAN MOBIL HONDA DI PONTIANAK (Studi Kasus Pelanggan Yang Memakai Mobil Honda) - B31109095, BUDHI SETIAWAN (Jurnal Manajemen Update, 2016)
This study aimed to determine and provide empirical evidence about whether the variable quality of product, price and brand image influence on purchase decisions Honda In Pontianak (case studies of customers who use the car Honda) This study used multiple linear regression analysis using SPSS 16. The population used is the public Pontianak with the criteria User Car Honda. The samples used were 100 people on the community of Pontianak by purposive sampling method. The results of multiple regression analysis that has been done shows that, Y = 0,311X1 + 0,276X2 + 0,308X3. The independent variables that most influence on the dependent variable is the variable quality of product (0,311), followed by a variable price (0.276 and the last is the variable of brand image (0,308). The results of the t test to prove that all the independent variables (product quality, price and brand image) has a positive effect on the dependent variable, namely the purchase decision honda car. the coefficient of determination (adjusted R2) obtained amounted to 0.633. this means 63.33% purchasing decisions are influenced by the variable quality of the product, price and brand image, and the remaining 36.67% influenced by other variables. Keywords: product quality, price, brand image and purchasing decisions.